If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 8(b + -5) Reorder the terms: 8 = 8(-5 + b) 8 = (-5 * 8 + b * 8) 8 = (-40 + 8b) Solving 8 = -40 + 8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8b' to each side of the equation. 8 + -8b = -40 + 8b + -8b Combine like terms: 8b + -8b = 0 8 + -8b = -40 + 0 8 + -8b = -40 Add '-8' to each side of the equation. 8 + -8 + -8b = -40 + -8 Combine like terms: 8 + -8 = 0 0 + -8b = -40 + -8 -8b = -40 + -8 Combine like terms: -40 + -8 = -48 -8b = -48 Divide each side by '-8'. b = 6 Simplifying b = 6
| 5x-2=-2+4x | | 61.25=0.15t+35 | | 1x+7=2x-3 | | 2-5x=-4x-2x | | 6(1+x)=24 | | 2n+n=9+6n+2-5 | | 3k-5=28 | | 2(6-q)=0 | | 6-2x-x=4x+6 | | .6m=6 | | 3(12-r)=30 | | 3(2x-6)+6(x-4)=-3(5-5x)+5x-17 | | 3x+7y+3=90 | | x^2+2x-81=0 | | -z+11=-7 | | -6x-x=-6-4x | | 0=6(10-a) | | 4k-2k-4= | | -5n-6=-5n-2n | | 8(9+t)=104 | | 6n-10=-2+8n | | 20=4(x+1) | | 2r-7=-11+r | | 3(c-2)=18 | | 8y+8=37y-7 | | 14=7(k-4) | | 5x-(4x+2)=2x-10 | | 2.6x+1.8=2.4x+22 | | 2(m-5)=8 | | -6x-12x=-126 | | 60x-9= | | 25=5(z+4) |